Impact modified PLA-hydroxyapatite composites – Thermo-mechanical properties - Akindoyo, John Olabode; Beg, M. D. H.; Suriati, Ghazali; Heim, Hans P.; Feldmann, Maik (Elsevier Ltd, 2018)
Synergistic composites from poly(lactic acid) (PLA) and hydroxyapatite (HA) hold great potential for load bearing applications. In this study, PLA-HA composites were produced through extrusion, and test specimens were subsequently prepared through injection molding. Impact properties of the composite was improved by incorporating different amount (0 to 15 wt%) of Biomax® Strong 120 (BS) impact modifier. The mechanical, thermal, morphological and dynamic mechanical properties of the resulting composite were investigated. Likewise, chemical interactions during blending were investigated through Fourier transforms infrared spectroscopy. Incorporation of BS decreased the crystallization activities at the PLA-HA interface, but with a right shift in crystallization temperature as the BS content increases. Also with increasing BS content, mechanical properties of the PLA-HA composite were reduced. However there is an obvious increment in impact strength (78%) and elongation at break (206%). The composite containing 5 wt% BS content presents the best compromise among the investigated properties.